Simulation of Wheatstone Bridge for Measurement of Resistances - Nigmet KOKLU; Dundar YENER; Hamdi Sukur KILIC (International Journal of Applied Methods in Electronics and Computers, 2015)
Vast developments in information and technology era necessitate implementation of technology reinforced teaching learning. Information and communication technologies remove the negative effects of preparation and understanding problems. Scientist admit that animations and simulations widely contribute education by learning through experience. Abstract courses like physics complicate comprehension of student therefore alternative teaching methods like animation and simulation are used. In this study, we had benefit of animations for achieving better comprehension on teaching Resistance Measurement with Wheatstone Bridge. Primarily, definitions about the topic are given as animations then, the simulation. Following the directions given to students, calculation of unknown resistance through entering values in simulation with aiming students to understand what Wheatstone bridge is used for. The bridge circuit is built in simulation on computer environment and calculation of the unknown resistance per student is procured by monitoring the change on galvanometer. Besides, derivation of the formulas are showed in animations aiming minimizing misconception about topic and better comprehension.